Functional Properties, Changes During Storage And Application Of "Duckrimi" (Surimilike Material From Duck Meat) On Sausage - Ismail, Ishamri (2010)

(untitled)
Quality characteristics of duck meat were studied through three stages. In the first stage, duck samples were treated with different number of washing cycles. In the second stage, duck meat was preserved with various types of cryoprotectant and in the final stage, duck meat was developed into surimi-based product i.e. sausage. Washing was found to reduce fat and protein content significantly. The quadruple washing resulted in the lowest cholesterol and myoglobin contents; but higher pH, folding score, expressible moisture and water holding capacity; at the same time reducing the gel strength of the sample.